2006
DOI: 10.1111/j.1748-1716.2006.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐site antagonism and pentobarbital actions do not depend on the α‐subunit type in the recombinant rat GABAA receptor

Abstract: The GABA-site antagonism does not depend on the subtype of alpha-subunits. Similarly, pentobarbital activates ternary receptors composed of different alpha-subunits in a bicuculline-sensitive manner. The potencies of bicuculline to inhibit pentobarbital-activated currents are identical with receptors containing alpha1, alpha4 or alpha5-subunit. The alpha1beta2 and alpha4beta2 receptors possess higher GABA potencies compared with the alpha1beta2gamma2L and alpha4beta2gamma2L receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…We have reported earlier that the GABA site antagonism and pentobarbital action on the recombinant rat GABA A receptor do not depend on the α‐ and β‐subunits 31 . In the present study, we found that the Hα 4 β 3 γ 2S receptor conferred lower agonist efficacies on GABA sites compared with the Hα 4 β 2 γ 2S receptor in terms of significantly reduced I max (Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…We have reported earlier that the GABA site antagonism and pentobarbital action on the recombinant rat GABA A receptor do not depend on the α‐ and β‐subunits 31 . In the present study, we found that the Hα 4 β 3 γ 2S receptor conferred lower agonist efficacies on GABA sites compared with the Hα 4 β 2 γ 2S receptor in terms of significantly reduced I max (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Drugs were bath applied from a common tip via a gravity‐driven multibarrel drug‐delivery system (ValveLink 16 pinch valve perfusion system controlled by a Valvelink 16 controller; AutoMate Scientific, San Francisco, CA, USA). Cells were clamped at −70 mV for all experiments and currents at the end of the 20 s drug application were measured for quantification of current amplitudes 30,31 …”
Section: Methodsmentioning
confidence: 99%
“…The predominant synaptic GABA A receptor isoform is composed of two ␣ 1 , two ␤ 2 , and a ␥ 2 subunits. Upon deletion of the ␥ 2 subunit and the inclusion of ␣ 4 , ␣ 5 , ␦, or ε subunits, GABA A receptors have an altered affinity for GABA and allosteric modulators, such as pentobarbital (7,10,23,53). We speculate that altered subunit stoichiometry provides a plausible mechanism for the pentobarbital insensitivity described here.…”
Section: Discussionmentioning
confidence: 76%
“…Classical benzodiazepines such as midazolam and diazepam are fairly nonselective, showing equally high efficacy at GABA A receptors containing alpha 1,2,3 and 5 subunits but no appreciable affinity at physiologically relevant concentrations for alpha 4 and 6 containing receptors (Harris et al, 1997). Likewise, barbiturates are fairly nonselective positive allosteric modulation of GABA A receptors (Harris et al, 1997; Pistis et al, 1997; Rahman et al, 2006). These results indicate that GABA A positive modulation is important for the discriminative stimulus effects of TCE, but do not suggest which subunits are involved.…”
Section: Discussionmentioning
confidence: 99%